DAMPAK COVID-19 TERHADAP PENDAPATAN OJEK ONLINE DI BANDA ACEH - Ardian Ardian; Muhammad Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
AbstractThis study aims to determine the income of online motorcycle taxis before and during the covid-19 pandemic. In this study, the authors used primary data with the data collection method using a questionnaire, the sample in this study was 84 online motorcycle taxi drivers in Banda Aceh City. The results showed that the income for online motorcycle taxis before the pandemic was around Rp. 2,000,000 up to Rp. 6,000,000 where the majority of online motorcycle taxis had income before the pandemic was Rp. 4,000,000 as much as 28.6 percent, during the pandemic online motorcycle taxi revenues averaged around Rp. 1,000,000 up to Rp. 4,000,000 where the majority of online motorcycle taxi drivers are Rp. 2,000,000 up to Rp. 2,500,000 as much as 16.7 percent and there is a significant difference in online motorcycle taxi revenues before and during the Covid-19 pandemic in Banda Aceh City (p0.05).  Keywords: Income, online motorcycle taxi, covid-19 pandemic